South Pole Station [large type] : a novel - Shelby, Ashley, 1977- (Wheeler Publishing, a part of Gale, a Cengage Company, 2017)
" Do you have digestion problems due to stress? Do you have problems with authority? How many alcoholic drinks do you consume a week? Would you rather be a florist or a truck driver? These are the questions that decide who has what it takes to live at South Pole Station, a place with an average temperature of -54°F and no sunlight for six months a year. Cooper Gosling is adrift at thirty, unmoored by a family tragedy and floundering in her career as a painter. So she applies to the National Science Foundation Artists & Writers Program and flees to Antarctica -- the bottom of the Earth -- where she encounters a group of misfits motivated by desires as ambiguous as her own. There's Pearl, the cook whose Carrot Mushroom Loaf becomes means toward her Machiavellian ambitions; the oxymoronic Sal (he is an attractive astrophysicist); and Tucker, the only gay black man on the continent who, as station manager, casts a watchful eye on all. The only thing they have in common is the conviction that they don't belong anywhere else. Enter Frank Pavano -- a climatologist with unorthodox beliefs. His presence will rattle this already unbalanced community, bringing Cooper and the Polies to the center of a global controversy and threatening the 800-million-year-old ice chip they call home. In the tradition of And Then We Came to the End and Where'd You Go Bernadette?, South Pole Station is a warmhearted comedy of errors set in the world's harshest place. "-- Provided by publisher.